2022
DOI: 10.3389/fgwh.2022.832880
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pregnancy Associated Malaria in India

Abstract: Malaria in pregnancy is a major public health concern. It results in impaired maternal health and adversely effects fetal and perinatal outcomes. The present systematic review was conducted to assess the prevalence, distribution and adverse pregnancy outcomes in malaria infected females in India. A comprehensive search and review of PubMed and Web of Science based on PRISMA guidelines was carried out to find articles reporting prevalence of malaria in pregnant women from India. Data from 16 studies were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…WHO strategies for MiP include SP-IPTp, ITNs, indoor residual spraying (IRS), and the detection and treatment of cases [3,9], which have not achieved the expected results and the frequency of MiP remains high. A meta-analysis with 14 studies from Colombia reported a prevalence of 16.7% [10]; a meta-analysis of 16 studies from India reported 11.4% [11], and in sub-Saharan Africa frequencies up to 45.8% have been reported [12].…”
Section: Introductionmentioning
confidence: 97%
“…WHO strategies for MiP include SP-IPTp, ITNs, indoor residual spraying (IRS), and the detection and treatment of cases [3,9], which have not achieved the expected results and the frequency of MiP remains high. A meta-analysis with 14 studies from Colombia reported a prevalence of 16.7% [10]; a meta-analysis of 16 studies from India reported 11.4% [11], and in sub-Saharan Africa frequencies up to 45.8% have been reported [12].…”
Section: Introductionmentioning
confidence: 97%
“…Its severity is underscored by its lethality, especially in young children and pregnant women. In 2019, the World Health Organization (WHO) reported an estimated 229 million malaria cases and 409,000 deaths, highlighting the urgent need for effective treatment alternatives 22 . Around 6.3 million cases were reported from the Southeast Asia region, majority of cases were present in India 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, 36 investigations between 1994 and 2019 reported prevalence from 5% to 60%, higher in adolescents and young people, with decreasing trend in urban areas [3]. In India, the systematization of 16 studies reported a combined prevalence of 11.4% [4]; in Colombia, it was 16.7% based on 14 studies [5]; and in Sub-Saharan Africa, the pooled prevalence of 35 studies was 26.1% [6].…”
Section: Introductionmentioning
confidence: 99%